Size and temperature effects on dielectric breakdown of ferroelectric films - Sheng Tong (Journal of Advanced Ceramics, 2021)
Abstract The paper introduces a model of dielectric breakdown strength. The model integrated thermal breakdown and defect models, representing the relationship between the electric field of ferroelectric films and dimensional parameters and operating temperature. This model is verified with experimental results of the lead lanthanum zirconate titanate (PLZT) films of various film thickness (d = 0.8–3 μm), electrode area (A = 0.0020–25 mm2) tested under a range of operating temperature (T = 300–400 K) with satisfying fitting results. Also learned is a relationship that the recoverable electric energy density is directly proportional to the square of breakdown electric field. This relationship is found viable in predicting the electric energy density in terms of variables of d, A, and T for the PLZT films.